Pengaruh Return on Asset dan Debt to Equity Ratio Terhadap Nilai Perusahaan Subsektor Makanan dan Minuman di Bursa Efek Indonesia - Annisa Juliartha Maharani; Roswaty Roswaty; Endah Dewi Purnamasari (Jurnal Bisnis, Manajemen, dan Ekonomi, 2021)
This study aims to measure the effects of return on assets (ROA) and debt to equity ratio (DER) on the firm value of the food and beverage sub-sector companies for the period 2016-2019. The total population was 26 and the final sample was 11 selected deploying purposive sampling technique. Financial report data were collected from www.idx.com. This study applied the multiple linear regression method to analyze data. The measurement results evidence that partially ROA has a significant effect while DER has no significant effect on firm value. Simultaneously, ROA and DER have no significant effect on firm value.